Single phase Cascaded H-Bridge Multilevel Inverter study and comparison of different levels (Journal of Madenat Alelem, 2018)
Multi-level inverter used in applications that require high power and medium voltage. It can be used in: homes, factories, as well as in the military and medical aspects. This paper deals with study of Cascaded H-bridge and comparison between different levels for this type (three level, five level and seven level are presenting in this study). The comparison based on the design, the cost and the total harmonic distortion. The design tends to be more complicated when increasing the number of levels because of using more sources, more H-bridges and more connection wires. The control becomes more complexity as well as the inverter will be expensive and heavy as compared to low levels. Considering to the results of Matlab\ Simulink which illustrate the total harmonic distortion is being low when increasing the level and this will be an important matter in the output voltage. The level number of multi-level inverter is choosing according to the type of load.
Keywords: Cascaded H-Bridge multilevel inverter, Sinusoidal pulse width modulation techniques